Time and frequency transfer with the ESA/CNES ACES-PHARAO mission. (5th March 2015) - Delva, P.; Le Poncin-Lafitte, C.; Laurent, P.; Meynadier, F.; Wolf, P.
Abstract: We have written a theoretical description of one-way and two-way satellite time and frequency transfer and developed a model of the micro-wave link in the frame of the ACES/PHARAO mission. This is used to write a data analysis software and a simulation to test it. A very short description of the mission and of the micro-wave link is given here. A detailed description can be found in Delva et al ., 2012, Proceedings of the EFTF, Gothenburg, Sweden, arXiv:1206.6239.